Board size and firm performance of listed companies in Indonesia - Juanda, Juanda; Jalaluddin, Jalaluddin (JURNAL MANAJEMEN, 2021)
The purpose of this research is to investigate the influence of board size on the financial performance of firms listed on the Indonesian Stock Exchange from 2014 to 2018. The research method uses multiple linear regression. The firm performance is measured with return on assets (ROA). The research result shows that board size does not significantly influence the firm performance. Therefore, it is implied that board size of listed firms in Indonesia is not proven either to improve or worsen the firm performance. This research is particularly important to the firms and their shareholders in Indonesia and other developing economies since it contributes to a better understanding of board size – firm performance relationship.